Emotional intelligence: a key aspect in the development of preschool children - Б. Матаев; А. Темиржанова; А. Бекишева; Ф. Омер (Хабаршы. Психология және социология сериясы)
This study explores the importance of emotional intelligence (EI) in the development of preschool-aged children. The aim of the research is to identify the key components of EI and develop a program for its enhancement. The scientific significance of the work lies in confirming the impact of EI on children's social skills, emotional well-being, and adaptation in society. The methodology includes observing children's behavior, conducting surveys with parents and educators, and testing children’s EI levels using standardized techniques. The results demonstrate that children with high EI manage their emotions better, resolve conflicts more effectively, and establish stronger interpersonal connections. This research contributes to understanding the critical role of EI in educational practices, particularly in preparing children for school. The study provides recommendations for parents and educators on fostering EI through games, teaching self-regulation skills, and encouraging emotional empathy. The practical value of the work lies in developing programs and resources to promote EI in preschool children.